Molecular and phenotypic effects of early exposure to an environmentally relevant pesticide mixture in the Pacific oyster, Crassostrea gigas. (1st June 2023) - Sol Dourdin, Thomas; Rivière, Guillaume; Cormier, Alexandre; Di Poi, Carole; Guyomard, Killian; Rabiller, Manuella; Akcha, Farida; Bah Sadialiou, Thierno; Le Monier, Pauline; Sussarellu, Rossana
Abstract: Early life stages are crucial for organism development, especially for those displaying external fertilization, whose gametes and early stages face environmental stressors such as xenobiotics. The pacific oyster, Crassostrea gigas, is considered a model species in ecotoxicology because of its ecological characteristics (benthic, sessile, filter feeding). So far studies have investigated the impact of xenobiotics at embryotoxic, genotoxic and physiological endpoints, sometimes at the multigenerational scale, highlighting the role of epigenetic mechanisms in transmitting alterations induced by exposure to single xenobiotics. However, to date, little is known about the impact of environmentally-mimicking contaminants cocktails. Thus, we examined the impact of an early exposure to environmentally relevant mixture on the Pacific oyster life history. We studied transcriptomic, epigenetic and physiological alterations induced in oysters exposed to 18 pesticides and metals at environmental concentration (nominal sum concentration: 2.85 μg.L −1, measured sum concentration: 3.74 ± 0.013 μg.L −1 ) during embryo-larval stage (0–48 h post fertilization, hpf). No significant differences in embryo-larval abnormalities at 24 hpf were observed during larval and spat rearing; the swimming behaviour of exposed individuals was disturbed, while they were longer and heavier at specific time points, and exhibited a lower epinephrine-induced metamorphosis rate as well as a higher survival rate in the field. In addition, RNA-seq analyses of gastrula embryos revealed the differential expression of development-related genes (e.g. Hox orthologues and cell cycle regulators) between control and exposed oysters. Whole-genome DNA methylation analyses demonstrated a significant modification of DNA methylation in exposed larvae marked by a demethylation trend. Those findings suggest that early exposure to an environmentally relevant pesticide mixture induces multi-scale latent effects possibly affecting life history traits in the Pacific oyster. Graphical abstract: Image 1 Highlights: Crassostrea gigas embryos were exposed to an environmental pesticide mixture for 48 h. Carry-over effects were observed along the lifecycle of the oysters. The expression of developmental genes was modified during the exposure. Exposed oysters exhibit a global DNA demethylation during and after the exposure window. Some phenotypic endpoints were impaired: swimming behavior, metamorphosis, field survival.